Biosafety and mental health: Virus induced cognitive decline - Chunxiao Du; Ge Li; Gencheng Han (Elsevier, 2023)
Biological agents threats people's life through different ways, one of which lies in the impairment of cognition. It is believed cognitive decline may result from biological agents mediated neuron damage directly, or from the activation of the host immune response to eradicate the pathogen. However, direct linkage between infections and cognitive decline is very limited. Here we focus on the mechanisms of how different biological virus or they induced systemic and local inflammation link to the cognitive impairment, focusing on the roles of activated microglia and several molecular pathways mediated neurotoxicity.